Genetic problems at present and their challenges in the future: Thalassemia as a model - I Wahidiyat; P A Wahidiyat (Paediatrica Indonesiana, 2006)
Compared to the infectious diseases, geneticdisorders are not so frequently encounteredin the clinic, so that there has been a trendthat they are neglected by people or evenby the authorities. Our government is still fightingagainst infectious diseases and nutritional disorders.The immunization programs of the government haveindeed reduced the occurence of many infectious dis-eases. Actually, the government has to begin to thinkhow to handle the emerging genetic disorders, afterhaving eradicating infectious diseases.